Narratives that Address Affective Forecasting Errors Reduce Perceived Barriers to Colorectal Cancer Screening - Dillard, Amanda (2010)
Narratives from similar others may be an effective way to increase important health behaviors. In this study, we used a narrative intervention to promote colorectal cancer screening. Researchers have suggested that people may overestimate barriers to colorectal cancer screening. We recruited participants from the US, ages 49–60 who had never previously been screened for colorectal cancer, to read an educational message about screening for the disease. One-half of participants were randomly assigned to also receive a narrative within the message (control participants did not receive a narrative). The narrative intervention was developed according to predictions of affective forecasting theory. Compared to participants who received only the educational message, participants who received the message along with a narrative reported that the barriers to screening would have less of an impact on a future screening experience. The narrative also increased risk perception for colorectal cancer and interest in screening in the next year.